Characterization of Erbium Doped Photonic Crystal Fiber - Farah Diana Mahad; Abu Sahmah M.Supa'at; David Ian Forsyth; Tong Sun; Asrul Izam Azmi (Universitas Ahmad Dahlan, 2016)
Photonic crystal fibers (PCFs) which exhibit unique and tremendous optical properties have been undergoing quick growth in recent years. Studies on the characteristics of various types of PCFs have been reported. However, characterization on erbium-doped PCF has not previously been investigated. Therefore, in this paper, an erbium-doped core PCF having 7 rings of hexagonal air holes has been modeled. A perfectly matched layer (PML) is modeled within the PCF structure and simulated using Finite Element Method (FEM) using COMSOL software. The PML is optimized by varying the radius and thickness of the layer. Modal properties of the PCF have been investigated in terms of its effective index of the supported fundamental mode, confinement loss and thickness of the perfectly matched layer. This erbium-doped PCF has a confinement loss of 1.0E-6 at 1500 nm and a maximum effective refractive index of 1.476. This paper gathers useful data, which could be used for studying the characteristics of a PCF.